Stresses around a miniscrew. 3-D analysis with the finite element method (FEM) - Geramy Allahyar (Sciendo, 2023)
Miniscrews used for absolute anchorage may induce stresses in the surrounding tissues that are dependent on their proximity to the miniscrew.